Tigecycline as Therapeutic Choice in the Treatment of Infections Caused by Multidrug-Resistant Organisms - A Mini Review - Kavya C; Apoorva Dev M (RGUHS Journal of Medical Sciences)
Tigecycline is a broad-spectrum antibiotic effective against multidrug-resistant MDR pathogens particularly in complicated intra-abdominal infections cIAIs and complicated skin and soft tissue infections cSSTIs. It is active against methicillin-resistant Staphylococcus aureus MRSA vancomycin-resistant enterococci VRE and extended spectrum beta-lactamase ESBL-producing Gram-negative bacteria. However it has limitations against intrinsically resistant organisms such as Pseudomonas aeruginosa Acinetobacter baumannii and carbapenem-resistant Klebsiella pneumoniae. The pharmacokinetics of tigecycline restricts its use in blood stream infections BSIs and pneumonia. Nevertheless combination therapy with colistin or carbapenems has been shown to improve outcomes in patients with BSIs. High-dose tigecycline regimens enhance efficacy but are associated with risk of adverse effects. Its role in stewardship programs is vital however the potential for resistance development necessitates judicious use preference for combination regimens and robust infection control measures.